Research Of Technological Parameters Of Pattern Cotton-Silk Knitting Fabrics - Musayev Nuriddin Muxitdinovich ,; Gulyayeva Gulfiya Harisovna,; Mukimov Mirabzal Mirayubovich (The American Journal of Engineering and Technology, 2020)
In recent years, the country has been actively working on the development of the textile, clothing and knitting industry, expanding the assortment and assortment of finished products, as well as supporting investment and export activities of the sector. In the article outlines the ways in which new knitted and knitted fabric can be used efficiently using local raw materials. Production of new types of knit fabrics using natural silk will not only expand the use of natural silk, but will also expand the range of knitted fabrics and improve their quality, consumption and especially hygienic properties. Manufactured cotton-silk knitted fabric was fabricated in a 18-gauage knitting machine made of Germany`s Mayer & Cie OVJA 1.6 ET. In the article results of analyses of technological parameters patterned knitted fabrics, worked out with purpose effective using of locals raw materials and produced